Gravidez na adolescência: perfil epidemiológico, fatores predisponentes e repercussões perinatais em uma maternidade pública de Goiânia – GO - Barbosa, Jony Rodrigues (2015)
The teenage pregnancy brings biological implications, family, psychological and economic, limiting or delaying social development opportunities for those young people. It also associates the probability of maternal and fetal complications, being seen as a public health problem. The aim of the study was to analyze the epidemiology, associated factors and perinatal outcomes of pregnant adolescents. It is a transversal and descriptive study consisted of a sample of 170 adolescents hospitalized for childbirth or conducting clinical abortion, during the period from August / 2013 to May / 2014 in a municipal public hospital in Goiânia, Goiás . The adolescents were interviewed during hospitalization for collecting data on the sociodemographic profile; gynecological and sexual history; knowledge about contraceptives; family and obstetric history; data from the current pregnancy and the newborn. The average age was 17.3 years, brown, live in own home with partners 3- 4 people in residence, household income 01-03 minimum wages, with a higher percentage of income among adolescents> 16 years. 30% (> 16 years) have formal or informal employment compared to 4% ( 16 years). 45.3% of teens have not completed high school. 91 (53.5%) were studying when they became pregnant and 59 (64.8%) dropped out of school during pregnancy. The menarche occurred between 11 and 13 years and the first sexual intercourse between 14-15 years (general group and> 16 years), respectively. The group 16 years, first sexual intercourse was 13-14 years (p = 0.009). The main reason for the first sexual act was the feeling by the partner. The amount of partners showed scattered data, ranging from 1 to 5. 99.4% know a contraceptive and 75.9% reported having first-degree relatives who have had children before age 20. The teenagers received support from family (85.9%), baby's father (82.4%) and paternal family (75.3%) from the beginning of pregnancy. 75.9% are still loving relationship with the baby's father. 69.4% of pregnancies were unexpected and 30.6% planned. 72.4% adolescents reported being the first pregnancy and reported having done prenatal consultations with 06. 53.6% reported having any complications during the pregnancy period. 61.8% of births were normal, 33.5% and 4.7% cesarean spontaneous abortions. Prevailed pregnancies up to 37 weeks, weighing the appropriate newborn with APGAR rates between 8 and 10. The site of the first feeding was in rooming in 81.9% of cases and about 60% of teens plan to breastfeed 1 year. It is suggested public prevention, through guidance in health and educational unit, to educate teenagers about the implications of pregnancy in their lives.